Pemanfaatan Media Sosial Instagram @Covermake_Id Untuk Peningkatan Penjualan Produk - Melinda Wijayanti; Asriyani Sagiyanto; Fajar Diah Astuti (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the utilization of the Instagram social media platform by the account @covermake_id in increasing product sales. As one of the most widely used digital platforms in Indonesia, Instagram holds significant potential as an effective marketing tool, especially in building brand image and reaching a broader audience. This research employs a descriptive qualitative approach with data collected through interviews, observations, and documentation. The findings indicate that @covermake_id effectively uses Instagram features such as feed posts, stories, reels, and Instagram Shopping to promote products, engage with customers, and enhance brand visibility. Additionally, the use of real-time marketing strategies that follow current trends helps attract audience attention. However, some challenges remain, including limited human resources in daily content management and suboptimal responsiveness to customer inquiries. In conclusion, the use of Instagram by @covermake_id has positively contributed to increased sales, although more structured and responsive social media management strategies are needed to maximize results.